Synthesis, characterization, luminescence study and Judd-Ofelt analysis of highly luminescent Eu(III) complexes - Ritu Langyan (Next Materials)
This paper reports the synthesis of three red luminescent Eu(III) complexes, featuring dimethyl propanedioate as the primary ligand and 4-methyl-1,10-phenanthroline and 2,2′-bipyridine as coligands. The synthesized complexes were thoroughly characterized using various techniques, including elemental analysis, ESI-MS+ , FT-IR, TGA-DTA, PXRD, FESEM, EDAX, UV-Visible spectroscopy, photoluminescence spectra, and decay time measurements. The photoluminescence properties of the complexes in powder and solution were investigated, revealing the dominant emission of the Eu(III) ion from the 5D0→7F2 transition, responsible for the characteristic red emission. The Judd-Ofelt theory was applied to analyse the emission spectra of the complexes. The results show high values of quantum yield, branching ratio, stimulated emission cross-section, and thermal stability for the complexes, indicating their potential as luminescent materials in laser and photonic devices.